A new ratiometric fluorescence assay based on resonance energy transfer between biomass quantum dots and organic dye for the detection of sulfur dioxide derivatives. Issue 71 (17th December 2019) - Zhao, Jingjin; Peng, Yao; Yang, Keqin; Chen, Yunyun; Zhao, Shulin; Liu, Yi-Ming
Abstract : A new ratiometric fluorescence assay has been developed for the detection of sulfur dioxide derivatives with repeatability and selectivity. The assay was applied to quantitate HSO3 − in cell lysates with accurate results. Abstract : Sulfur dioxide (SO2 ) is considered as the fourth gas signal molecule after nitric oxide (NO), carbon monoxide (CO) and hydrogen sulfide (H2 S). It plays important roles in several physiological processes. Therefore, the design and synthesis of nanoprobes for the detection of SO2 derivatives in cells is of great significance. Herein, we report a new ratiometric fluorescence nanoprobe based on resonance energy transfer (RET) between biomass quantum dots (BQDs) and organic dye (DMI) for the detection of SO2 derivatives. The proposed ratiometric fluorescence assay allows the determination of HSO3 − in the range of 1.0 to 225 μM with a detection limit of 0.5 μM. Importantly, the proposed ratiometric fluorescence nanoprobe exhibits a high photostability and good selectivity for HSO3 − over other chemical species including H2 S and biological mercaptans. Quantitation of HSO3 − in cell lysates by using the nanoprobe is demonstrated.